Lymphocyte‐activation gene 3 expression associates with poor prognosis and immunoevasive contexture in Epstein‐Barr virus‐positive and MLH1‐defective gastric cancer patients. Issue 3 (12th November 2020) - Lv, Kunpeng; Li, Ruochen; Cao, Yifan; Gu, Yun; Liu, Xin; He, Xudong; Jin, Kaifeng; Fang, Hanji; Fei, Yuchao; Shi, Mingsu; Liu, Hao; Li, He; et al.
Abstract: Lymphocyte activation gene 3 (LAG‐3) is a transmembrane immune checkpoint that facilitates immune escape via suppressing T‐cell‐mediated anti‐tumor immunity. The role of LAG‐3 in gastric cancer is little known. Consequently, we assessed the clinical significance of LAG‐3 in gastric cancer. In our study, patients with gastric cancer from Zhongshan Hospital ( n = 464) and data from the Asian Cancer Research Group ( n = 300) were analyzed. LAG‐3 + cell infiltration and other immune contexture in gastric cancer were detected by immunohistochemistry. Kaplan‐Meier curves and log‐rank test were used for survival analyses. Intratumoral LAG‐3 + cells mainly accumulated in Epstein‐Barr virus (EBV)‐positive (EBV subtype) and MLH1‐defective (dMLH1 subtype) gastric cancer. Furthermore, LAG‐3 + cell infiltration was strongly associated with inferior clinical outcomes in patients with these two subtypes of gastric cancer. Moreover, we found intratumoral LAG‐3 + cell high infiltration was associated with an immunoevasive contexture featured by decreased IFN‐γ + cells and perforin‐1 + cells, but increased regulatory T cells and M2‐like macrophages in EBV/dMLH1 subtype of gastric cancer. LAG‐3 was a poor prognostic factor and might be a potential immunotherapeutic target in EBV‐positive and MLH1‐defective gastric cancer. Abstract : What's new? Immunotherapies targeting factors involved in the regulation of immune responses are effective against several cancers. In the case of gastric cancer, however, clinical trials suggest that a majority of patients fail to respond to existing immunotherapies, warranting a search for novel targets. Here, the authors assessed the clinical relevance of lymphocyte activation gene 3 (LAG‐3), a transmembrane receptor linked to prognosis in different cancer types. Immunohistochemistry and molecular analyses of patient tissue samples show that LAG3 expression is indicative of poor prognosis particularly in Epstein‐Barr virus‐positive and MLH1‐defective gastric cancer. The findings point to LAG3 as a promising immunotherapeutic target.